Trusting outsiders to do your research how does industry learn to do it? - MacLachlan, Alexander
Alexander MacLachlan describes Du Pont's experience in partnering with universities and other institutions.
Top R&D leadership recognizes that leveraging external resources is critical. A Du Pont veteran explains why-and how.
Success in the global marketplace requires restructuring and rethinking of all aspects of business management, including, in the case of technology-based companies, how technology itself is acquired and improved. Because new technology development is often so risky in either cost or time to the marketplace, and is available from so many external sources, it is vital that companies learn how to tap into these external sources as effectively as they have managed their own internal R&D organizations for so long. These external sources include partnerships with other companies, universities and research institutes and various government laboratories and development facilities a unique opportunity at this time in history, as our great university and government laboratory systems are being driven by similar global pressures to team up with us in new and more effective ways.
Keywords: Research